2014
DOI: 10.1002/jcph.274
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of the 5‐hydroxymethyl metabolite of tolterodine after administration of fesoterodine sustained release tablet in western and east Asian populations

Abstract: This analysis was conducted to investigate factors that affect 5-hydroxymethyl tolterodine (5-HMT) pharmacokinetics after administration of fesoterodine sustained release tablets to Westerners and East Asians. Ten pharmacokinetic studies and three efficacy/safety studies in overactive bladder (OAB) patients were pooled for the population pharmacokinetic analysis. The plasma 5-HMT concentration data were described by a 1-compartment model with first order absorption and a lag time. Creatinine clearance (CLCR), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Additionally, the third most common anticholinergic medication was tolterodine, which is metabolized primarily by CYP2D6 and secondarily by CYP3A4 . Interestingly, a pharmacokinetic study comparing the metabolite for tolterodine in East Asian and Caucasian populations found that there was increased clearance in Japanese subjects, although there was no significant difference in exposure to the metabolite . We note that the most commonly used anticholinergics found in this study were not necessarily used less frequently in the Asian patients that received anticholinergics, but we hypothesize a decreased use of these medications in the Asian population in general compared to the Caucasian and Hawaiian populations.…”
Section: Discussionmentioning
confidence: 51%
“…Additionally, the third most common anticholinergic medication was tolterodine, which is metabolized primarily by CYP2D6 and secondarily by CYP3A4 . Interestingly, a pharmacokinetic study comparing the metabolite for tolterodine in East Asian and Caucasian populations found that there was increased clearance in Japanese subjects, although there was no significant difference in exposure to the metabolite . We note that the most commonly used anticholinergics found in this study were not necessarily used less frequently in the Asian patients that received anticholinergics, but we hypothesize a decreased use of these medications in the Asian population in general compared to the Caucasian and Hawaiian populations.…”
Section: Discussionmentioning
confidence: 51%
“…Based on a population pharmacokinetic analysis, renal impairment, hepatic impairment, CYP2D6 genotype, and concomitant CYP3A4 inhibitors/inducers were identified as factors impacting 5-HMT exposure after fesoterodine administration 27 . A large randomized, double-blind, placebo and active (moxifloxacin) controlled trial in healthy adults that evaluated the effects of fesoterodine on cardiac repolarization indicated that fesoterodine 4 mg (therapeutic dose) and 28 mg (supratherapeutic dose) administered once daily for 3 days did not prolong the Fridericia's corrected QT (QTc) interval from baseline versus placebo 28 . The positive QTc prolongation by moxifloxacin confirmed the sensitivity of the study.…”
Section: Studymentioning
confidence: 99%
“…The key results of the 15 retained articles [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] on the pharmacology of oral fesoterodine are summarized in Table 1. After single or multiple dosing of oral fesoterodine 4 mg to 28 mg once daily, plasma concentrations of the active metabolite 5-HMT are proportional to the dose 16,17 .…”
Section: Pharmacologymentioning
confidence: 99%
“…A placebo‐controlled clinical trial demonstrated the efficacy and safety of imidafenacin for the treatment of OAB in Japanese patients. However, there is a lack of data for imidafenacin in the Caucasian population, and there might be differences in pharmacokinetics and behavioral habits between Western and East Asian patients …”
Section: Introductionmentioning
confidence: 99%
“…However, there is a lack of data for imidafenacin in the Caucasian population, and there might be differences in pharmacokinetics and behavioral habits between Western and East Asian patients. 8 This study aims to evaluate the efficacy and safety of imidafenacin compared with those of standard treatment with tolterodine in Caucasian patients with OAB.…”
Section: Introductionmentioning
confidence: 99%